COLONIALISM, INDEPENDENCE AND DIGITAL TECHNOLOGY - Toupin, Sophie; Nikoi, Nii Kotei Nikoi; Mare, Admire; Willems, Wendy (AoIR Selected Papers of Internet Research, 2021)
Conventionally, the African continent is largely written out of accounts on technology. If discussed, technology is often framed as the result of outside influences or the product of technology transfer from the West but rarely are Africans taken seriously as makers or active users of technology (Mavhunga, 2014, 2017). Recent work on race and technology has been useful in highlighting the contribution of Black people to the development of digital technology (McIlwain, 2020) and the creative deployment of technology (Brock, 2020) but has not always engaged extensively with longer histories of racialization and transnational dimensions of Blackness. Ongoing debates on platform imperialism (Jin, 2013) and data colonialism (Couldry and Mejias, 2019) have been important in demonstrating the disproportionate levels of power that global social media platforms continue to wield and the lingering importance of technology in extractive practices. However, these political economy approaches have insufficiently acknowledged spaces for agency nor have they examined the way in which the state impinges on the everyday lives of citizens. The four papers in this panel deploy the notion of independence to make sense of the way in which Africans have created, used and imagined digital technology. They treat digital technology as potential tools for liberation as well as constitutive of spaces that enable reflection on what it means to be independent. The panel regards the freedoms occasionally made possible by digital technology as always subject to the constraints imposed by powerful actors such as the (post)colonial state and corporate social media platforms.